Metribuzin mobility in soil column as affected by environmental and physico-chemical parameters in Mumias sugarcane zone, Kenya - Lagat, S C; Lalah, J. O; Kowenje, C. O.; Getenga, Z. M (Asian Research Publishing Network (ARPN)., 2011)
The physico-chemical parameters of soil, influences the soil solution characteristics and that may affect the sorption of soil applied herbicides. The present investigation reports the influence of physico-chemical parameters sorption and leaching of metribuzin, a triazine herbicide. The Kf (Freundlich adsorption coefficient) values of metribuzin were 14.9 µg/K which suggests that sorption as a function of herbicide concentrations and (1/n) value of 0.20 µg/L reflecting the degree of sorption of the herbicide. For leaching the amounts of metribuzin leached were 89.83% of applied quantity this is due to effects of various physicochemical factors and climatic conditions in tropical soils. The study concludes that less than 10.17% of applied metribuzin remains in the soil. However from agricultural point of view, the amounts are trivial, but from environmental (including potential ground water contamination) point of view, small residues are important factors to consider.
Keywords: Metribuzin; Sorption; Leaching; Ttropical soils